Digital calorimeter for measuring the specific heat of liquids. Issue 1 (1st January 2022) - Azhar; Melita, A S; Doyan, A; Susilawati; Ayub, S; Hudha, L S
Abstract: The purpose of developing this digital calorimeter is to make a temperature measuring device using Arduino Uno that can be used for physics practicum at the Physics Laboratory of the University of Mataram. This tool is designed according to the function of the calorimeter. Calorimeter is a tool used to determine the heat capacity, specific heat capacity, and latent heat capacity of an object or material. In making this digital calorimeter, the ds18b20 sensor is used to measure the temperature of the liquid, when the sensor is inserted into the calorimeter, it will be able to read the temperature rise that occurs in it. The graph is obtained from the relationship between time (t) and heat energy (Q), it can be seen that the longer the liquid is given electrical energy, the higher the heat generated.